Biomechanical similarities of longswings at varying speeds and the kovacs action - Low, C.; Cooke, C. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
INTRODUCTION: Low movement variability in the backward longswing has been partly attributed to external competitive constraints (Irwin & Kerwin, 2005). However, a number of high level skills (e.g. Gienger, Deff, Kovacs) derive from variations in the longswing action. If movement variability is viewed as having a functional role (Bartlett et al., 2007) then variability in the longswing might be beneficial to subsequent skill acquisition. This study aims to determine whether variations in the speed of longswing can induce movements that are more similar to movements associated with a high level skill, in this case the Kovacs.